Teori Hukum Era Robert Nonet dan Philip Selznick Serta Relevansinya Terhadap Pembangunan Berkelanjutan di Indonesia - Shela Zulfa Syifaurrohmah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the relationship between the concept of responsive law developed by Robert Nonet and Philip Selznick and the benefits of sustainable development in the context of Indonesian law. Using normative legal research methods, this study focuses on the study of legal doctrines, scientific literature, and regulations related to sustainable development. The results of the study show that responsive law has the potential to become a more adaptive and participatory regulatory framework. This legal model is relevant to strengthening sustainable development policies because it supports the integration of social values, environmental protection, and intergenerational justice. However, structural challenges such as bureaucracy, regulatory inconsistency, and weak law enforcement remain obstacles to the implementation of responsive law in Indonesia. This study confirms that the application of responsive law can increase the effectiveness of sustainable development policies when developed in conjunction with the strengthening of national legal institutions.